Prevalence and pattern of dermatological manifestations among substance users across Kashmir Valley in North India - Aaqib Aslam; Shagufta Rather; Arshad Hussain; Faizan Younus; Najam U Saqib; Iffat Hassan (Wolters Kluwer Medknow Publications, 2022)
Background: Substance use has turned out to be one of the growing social problems of the present society cutting across all sorts of boundaries of the world with Kashmir Valley being no exception to this growing pathological phenomenon. Aims and Objectives: To find the prevalence and pattern of dermatological manifestations among substance users across Kashmir Valley. Materials and Methods: Cross-sectional study where patients of all age-groups, irrespective of gender, were enrolled in the three largest districts of Kashmir Valley over a span of 18 months. Results: Sample size was 710 with a male/female ratio of 12.4:1. The mean age of the cases was 25.2 ± 7.05 years. Heroin, one of the opioids, was the most common substance used (n = 515), followed by cannabis (n = 334). Pruritus was found to be the most common dermatological manifestation overall and statistically significant among heroin users. Stigmata of injection drug use (IDU) with the presence of track marks and sooting tattoos (93.1%), atrophic scars secondary to skin popping (30.7%), active skin ulcers (18.8%), and puffy hand syndrome (8.7%) were specifically seen among injection drug users. Oral involvement was seen in 48.5%, including periodontal disease, oral thrush, and stomatitis nicotinica. Hyperhidrosis was present in 30%, and hesitation cuts over arms in 16.3% of all substance users. Conclusion: Dermatological manifestations are quite prevalent among substance users in the population of Kashmir. Pruritus with temporal relation to substance use, stigmata of injectable drug use including track marks and sooting tattoos, atrophic scars at injection sites, active skin ulcers, and skin and soft tissue infections, and hyperhidrosis are among important dermatological clues for detecting substance use. Recognition of such cutaneous signs is important in these cases for more effective diagnosis and treatment.